If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9h + -6 + 12h + 20 = 22 Reorder the terms: -6 + 20 + -9h + 12h = 22 Combine like terms: -6 + 20 = 14 14 + -9h + 12h = 22 Combine like terms: -9h + 12h = 3h 14 + 3h = 22 Solving 14 + 3h = 22 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 3h = 22 + -14 Combine like terms: 14 + -14 = 0 0 + 3h = 22 + -14 3h = 22 + -14 Combine like terms: 22 + -14 = 8 3h = 8 Divide each side by '3'. h = 2.666666667 Simplifying h = 2.666666667
| 47-2x=-80-8x | | 53+6x=63+5x | | 6a-4/2a+2=2 | | 2x-5+4x=4x+10+36 | | -8x-7+8x=-3 | | 3p+4= | | 7(5-x)=-4(x-11) | | 3x^2+4x+1=65 | | a/2+a/2=3a+14 | | 10x^2-11x-12=0 | | 25t-5t^2-120=0 | | 5t^2-20t+15=0 | | 2x^3-3x-12x=0 | | 1+5x=19-x | | 9x+5y+6z-5x+4z-6y= | | x(x-10)=-21 | | Q=9xv | | 60=70-x | | 3s+18=3(s+6) | | -10(3y-5)=-30Y+50 | | 7x+2(x+5)= | | 8(9+5*3)= | | 21y+6=12 | | 7x+2(x+2)= | | 12+8=52 | | 0=x^4-2x^2+3 | | 0=4x^3+3x^2 | | 8(x+4)-4=4x-1 | | 5a+30=10a+5 | | 9m(4-3m)=0 | | -4(4a+8)=-16a-32 | | -4sinx+2=0 |